Guidebook for environmental and natural resources accounting methods and procedures. (Department of Environment and Natural Resources, 1993)
A manual on resource accounting to aid policymakers, students, researchers and advocates for Philippine natural resources. Includes definition of terms, physical account procedures, valuation methods, data requirements and sample computations. Also refer to "Guide to Environmental Accounting and Policy Development: The ENRAP Experience" for a more detailed explanation of the framework and policy applications governing this work.